Evolution and Population Structures of Prevalent Methicillin-Resistant Staphylococcus aureus in Taiwan - Chen, Chih-Jung; Yang Lauderdale, Tsai-Ling; Huang, Yhu-Chering (Frontiers in Microbiology, 2021)
Global methicillin-resistant Staphylococcus aureus (MRSA) strains were dominated by few genetic lineages, suggesting their inherent advantage of competitive fitness. The information of genome evolution and population structures of prevalent MRSA strains can help gain a better understanding of the success of the pandemic clones. Whole-genome sequencing was performed in 340 MRSA isolates belonging to three prevalent lineages, including ST59 (129 isolates), ST239/241 (140 isolates), and ST5 (71 isolates), collected from 1996 to 2016 in Taiwan. The time-scaled phylogeny and evolutionary pathways were estimated by Bayesian analysis using Markov chain Monte Carlo. The toxome, resistome, and plasmids were characterized by screening the raw reads with a public database. ST59, ST239/241, and ST5 MRSA were estimated to emerge in 1974, 1979, and 1995, respectively, in Taiwan. ST59 evolved through two major pathways, generating two subclones in 1980 and 1984. Both ST59 subclones remained prevalent in the healthcare and community environments in late 2010s. ST239/241 diverged into three subclones, respectively, in 1989, 1993, and 1995. The 1995-emerging ST239 subclone predominated after 2000 by replacing two previous early subclones. ST5 could be subdivided into two clades within 3 years of introduction, but no substantial difference of genomic profiles was identified in the strains of distinct clades. Each of the three pandemic MRSA lineages harbored its own specific toxome, resistome, and plasmids. The frequently identified genetic diversities between the subclones of the same lineage were genes mediating immune evasion, leukocidins, enterotoxins, and resistance to aminoglycosides. In conclusion, MRSA ST59 and ST239/241 emerged in the 1970s and evolved drastically during 1980 and 1995, resulting in three successful subclones prevailing in Taiwan. ST5 was introduced late in 1995 without a significant genetic drift during 20 years of evolution.